The polarographic determination of trace elements in blister and refined copper - Eve, Adrian John (Rhodes University, Faculty of Science, Department of Chemistry, 1954)
In the complete analysis of copper the following impurities are generally determined: silver, gold, lead, arsenic, antimony, selenium, tellurium, iron, zinc, cobalt, nickel, oxygen, sulphur, and, less commonly, tin and phosphorus. The actual copper content varies around 99.0% in blister copper; in the refined metal the content is somewhat higher, usually over 99.9%. The concentrations of the individual impurities vary from tenths to thousandths of one per cent.
Keywords: Copper; Polarographs; Polarography